Development Of Mathematics Spin Wheel Learning Media Flat Building Materials for Elementary Students - Hidayat, Rahmad; Ritonga, Rudi (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
This study aims to develop mathematics learning on flat shapes using a rotating wheel in elementary school students. Research method that is used is Research and Development of the ADDIE development model. This research was conducted in one of elementary school in South Jakarta, this research and development showed the results: 1) The development of a flat shape math wheel media was made based on the needs and characteristics of elementary school students. The design of the mathematics spin wheel learning media that the researchers made is very interesting because it develops innovations including 3D image shapes and various color choices, 2) The validity of the research and development of the math spin wheel media flat shape material has been validated by several expert whose results in average score is 90% with very valid criteria. 3) The level of effectiveness in the research and development of the mathematical rotary wheel media on flat shape materials was tested on a limited pilot trial and extensive trial. In limited pilot trial the researcher got an N-Gain value of 0.4 from the results of 6 students. Furthermore, in extensive trial, the researcher calculated the effectiveness by measuring the comparison of the pre-test and post-test and then calculated using the N-Gain formula and scored 0.82 and was included in the category of high effectiveness (effective). the results and conclusions of this research is flat shape math wheel media could be implemented in elementary school.